P. K. Feyerabend: prekračovanie obzorov, či deštrukcia vedy? - Jablonický, Pavol (Organon F, 2004)
The aim of the paper is to give an outline of the development of Feyerabend´s thought through four basic periods: the realist-empiricistic, intermediate, relativist and, finally, process-realistic periods. The ideas Feyerabend presents in his papers are often misunderstood and misinterpreted. The author attempts at revaluation of his work within the philosophy of science and to show the applicability of his ideas in problem solving in contemporary philosophy, epistemology and methodology of science as well as in other areas of sciences – e. g. anthropology or cognitive sciences. In his view Feyerabend´s ideas are still valid especially in analyses concerning different approaches to the problems of scientific realism, connections between perception and cognition, and comparability of radically different scientific conceptions (types of rationality etc.).